Requirements for applying data mining in auditing Identifying audit risks as a model - ramo, waheed mahmoud; al nuaymi, abdelwahid ghazi (Journal of Research in Finance and Accounting, 2021)
The research aims to propose a model that includes the components and steps necessary to apply data mining in the field of auditing in general and identify audit risks in particular, with an indication of the interest of professional organizations in data mining, the fields and uses of exploration in accounting and auditing, and the importance and impact of exploration on auditing and on the risk identification process. Among the most important results that have been reached is that the requirements for the application of data exploration proposed by the researchers are general observations, which can be guided in any environment and are not specific to a specific specialty or field, but the specificity of the audit has been taken into consideration more, and some requirements can be added that the auditor or accountant sees It is necessary and important to his work environment. As for the use of data mining in the field of audit risk, the matter is not related to a specific tool or method. Rather, there is more than one tool and method that can be used in this area.